2021
DOI: 10.3390/su13137375
|View full text |Cite
|
Sign up to set email alerts
|

Integrated GIS-Based Multi-Criteria Analysis for Groundwater Potential Mapping in the Euphrates’s Sub-Basin, Harran Basin, Turkey

Abstract: The Harran Basin is an important region where agricultural activities have been conducted for millennia. The agricultural water needs of the basin are largely met with surface irrigation through the GAP (South-Eastern Anatolian Project), while groundwater is used in some regions as potable water, tap water, and irrigation water. In this study, the groundwater potential of the Harran Basin was determined through the “GIS-based Multi-Criteria Decision Making (MCDM)” Method. Ten criteria were considered: Land Use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Deterministic interpolation comprises global polynomial (GPI), local polynomial (inverse distance weighted (IDW)), planar spline, and local polynomial interpolation (LPI) (Zandi et al, 2011;Ahmadian and Chavoshian, 2012). The posterior method can be used to correct the local errors without reducing the accuracy, the precision of the method is close to the Kriging techniques (Gunarathna, et al, 2016;Al-Omran et al, 2017;Aslan and Çelik, 2021). A considerable amount of literature has been published on water quality in Egypt, including many topics such as water quality assessment and groundwater pollution (Sabry, et al, 2019) but there were no reported researches on the investigation and verification of hydrogeochemical processes of water resources using statistical techniques.…”
Section: Introductionmentioning
confidence: 85%
“…Deterministic interpolation comprises global polynomial (GPI), local polynomial (inverse distance weighted (IDW)), planar spline, and local polynomial interpolation (LPI) (Zandi et al, 2011;Ahmadian and Chavoshian, 2012). The posterior method can be used to correct the local errors without reducing the accuracy, the precision of the method is close to the Kriging techniques (Gunarathna, et al, 2016;Al-Omran et al, 2017;Aslan and Çelik, 2021). A considerable amount of literature has been published on water quality in Egypt, including many topics such as water quality assessment and groundwater pollution (Sabry, et al, 2019) but there were no reported researches on the investigation and verification of hydrogeochemical processes of water resources using statistical techniques.…”
Section: Introductionmentioning
confidence: 85%
“…The AHP technique, which was used to determine the ranking of individual themes and the class weights, is most often used in multicriteria decision analysis for natural resource management, site selection, suitability analysis, etc. (Arunbose et al, 2021; Aslan & Çelik, 2021; Doke et al, 2021; Roy et al, 2022; Verma & Patel, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…The World Bank estimated in 2014 that Sri Lanka's annual freshwater withdrawals were 13 billion cubic meters [15]. Water shortage is the foremost issue in the country's dry zone [16][17][18][19], where there is a significant demand for water to irrigate 85% of the land to boost agricultural productivity [20,21]. Although Sri Lanka has six types of aquifers and a wide range of geological and hydrogeological settings in its 65,610 km 2 territory, groundwater extraction for agricultural purposes has long been restricted to the districts in the Northern Province (Jaffna, Kilinochchi, Mullaitivu, Vavuniya, and Mannar), that lack a perennial surface water resource [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Incorporating RS and GIS into groundwater potentiality mapping allows for data storage, manipulation, and analysis [44,47]. Integrated GIS and RS with AHP prove that it is a handy tool for delineating potential groundwater zones by reducing time and cost [4,17,32,37,41,44,45,[48][49][50]. Researchers adopt various techniques for delineation potential groundwater zones: statistical method [51], influence factor (IMF) [36,38,40,52], groundwater modelling, the combination of GIS, RS with AHP [37,41,45,49], and GIS-based machine learning [39,53,54].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation